Physical Factors and Microbubble Formation Explain Differences in CH4 Dynamics Between Shallow Lakes Under Alternative States - Baliña, Sofia; Sánchez, Maria Laura; del Giorgio, Paul A. (Frontiers in Environmental Science, 2022)
Submerged macrophytes play a key role in maintaining clear vegetated states in shallow lakes, but their role on methane (CH4) dynamics is less explored. They might enhance methanogenesis by providing organic matter but they may supply oxygen to the sediments increasing methanotrophy. They may also affect gas exchange by diminishing wind turbulence in the water column. We previously measured seasonal CO2 and CH4 partial pressure (pCO2 and pCH4) and diffusive fluxes from two clear vegetated and two turbid algal shallow lakes of the Pampean Plain, Argentina, and we reported that clear lakes had higher mean annual pCH4 despite states having similar mean annual CH4 diffusive flux. In this study we explore the contribution of physical and biological factors regulating surface pCH4. Mean annual CH4 diffusive fluxes and CH4 fraction of oxidation (Fox) were similar between states, implying a comparable mean annual CH4 input. kCH4 was significantly higher than kCO2, suggesting occurrence of CH4 microbubbles, yet kCH4 was higher in turbid lakes than in clear lakes, implying a higher microbubble formation in turbid lakes. Furthermore, in turbid lakes there were positive relationships between k and wind speed, and between k and pCH4, yet in clear lakes these relations were absent. Results suggest that submerged vegetation suppresses wind induced turbulence in clear vegetated lakes, decoupling kCH4 from wind and reducing microbubble formation, therefore augmenting pCH4 in their surface waters. Overall, physical rather than biological factors appear to control the observed differences in pCH4 between states.